The Effectiveness of Using the Six Thinking Hats in Acquiring Physical Concepts among Tenth Graders Based on their Achievement Motivation - Intesar G. Tannous; Moham'd M. AL-Dlalah (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: The study aims to investigate the effectiveness of using the Six Thinking Hats Strategy in acquiring physical concepts for tenth grade students in the light of their achievement motivation compared to the traditional method. Methods: quantitative descriptive Approach was employed.The study sample consisted of (55) female students, that were selected from one school within the Education Directorate in Madaba for the academic year 2020/2021. The sample was divided into two groups: experimental group (28) students which studied using the Six Thinking Hats strategy, and a controlled group (27) students which studied using the traditional method. Data were collected by classifying students according to their achievement motivation into high and low achievement motivation based on the achievement motivation scale. The researcher used the quasi-experimental approach. The test of acquiring physical concepts was applied after determining the validity and reliability of the study tool. Results: The result showed that there were statistically significant differences (α=0.05) due to the method of teaching in acquiring physical concepts in favor of the experimental group. The results also showed that there were statistically significant differences (α=0.05) attributed to achievement motivation in favor of female students with high achievement motivation, and there was no statistically significant difference in the interaction between them. Conclusions: The need of universities to carry out further studies in order to enforce the result of the study.